Monilethrix: A rare case diagnosed by dermoscopy - Aditya Rajendra Holani; Nishigandha S Haridas; Nirali G Shah; Nitin Chaudhari (Wolters Kluwer Medknow Publications, 2020)
Monilethrix is a rare genodermatosis characterized by hair shaft dysplasia, which is responsible for hypotrichosis. We present the case of a 2-year-old female, with involvement of the scalp, eyebrows, and eyelashes, in whom dermoscopy enabled a rapid diagnosis of monilethrix. Dermoscopy revealed the zones of intermittent constriction of the hair shaft, separated by elliptical nodes at regular intervals, giving the appearance of a characteristic "regularly bended ribbon" sign. This helped in differentiating it from pseudomonilethrix and other causes of hypotrichosis.